Health professionals perception and beliefs about drug- related problems on polymedicated older adults- a focus group study - Plácido, Ana (2021)
Background: Polymedicated older patients are at greater risk of suffering from adverse events. For this reason, the detection of both inappropriate polypharmacy and polypharmacy-associated Drug-Related Problems (DRPs) are essential to improve the health and wellbeing of older adults and to reduce healthcare costs. This work aims to explore health professionals' perceptions and opinions about polypharmacy and the handling of medicines by polymedicated older adults. Methods: Thirteen focus groups with 94 health professionals (20 community pharmacists, 40 general practitioners and, 34 nurses) were conducted in primary healthcare centers of the center region of Portugal. Participants were asked to discuss their perceptions and beliefs concerning DRPs in polymedicated older adults. The sessions were audiotaped. After the transcription and coding of focus group sessions, a thematic analysis was done. Results: The following four main themes emerged from the 13 focus group sessions: poor compliance and polypharmacy- A perpetuated vicious cycle, organization of the healthcare system, interaction and communication between the health professionals, and strategies to prevent inappropriate polypharmacy. Conclusions: The lack of both an efficient network of information and Interaction and communication between Health professionals makes the detection and/ or prevention of polypharmacy in older adults difficult. The implementation of new models to manage and/or prevent polypharmacy based on health professional perception and beliefs is essential to prevent DRPs and improve compliance among older adults.